Hypoxia inducible factors regulate hepatitis B virus replication by activating the basal core promoter - Wing, PAC; Liu, PJ; Harris, JM; Magri, A; Michler, T; Zhuang, X; Borrmann, H; Minisini, R; Frampton, NR; Wettengel, JM; Mailly, L; D’Arienzo, V; et al. (Elsevier, 2021)
Background and Aims: Chronic hepatitis B virus (HBV) infection is a major cause of liver disease and hepatocellular carcinoma. Hypoxia inducible factors (HIFs) are a hallmark of inflammation and are key regulators of hepatic immunity and metabolism and yet their role in HBV replication is poorly defined. HBV replicates in hepatocytes within the liver, a naturally hypoxic organ, however most studies of viral replication are performed under conditions of atmospheric oxygen, where HIFs are inactive. We therefore investigated the role of HIFs in regulating HBV replication.